1989
DOI: 10.1021/jo00264a047
|View full text |Cite
|
Sign up to set email alerts
|

Facile and convenient syntheses of quinones from phenols

Abstract: Two new highly effective and simple methods of oxidn. of dihydroxybenzenes and 2,6-disubstituted phenols lead to the corresponding quinones. The oxidn. is performed by hydrogen peroxide and catalyzed by halogens or hydrogen halides. The role of halogen catalysis is discusse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 1 publication
0
40
0
1
Order By: Relevance
“…2b Prepared according to the general procedure discussed above: eluent, EtOAc/n-hexane (20%); isolated yield = 0.042 g, 85%; white solid; 1 2-Phenyl-4H-chromen-4-one (2f). 2b Prepared according to the general procedure discussed above: eluent, EtOAc/n-hexane (20%); isolated yield = 0.047 g, 95%; white solid; 1 H NMR (600 MHz, CDCl 3 ) δ = 8.24 (d,J = 7.8 Hz,1 H),2 H),1 H),4 H),1 H), 6.83−6.84 ppm (m, 1 H); 13 C NMR (150 MHz, CDCl 3 ) δ = 179. 5, 164.4, 157.3, 134.8, 132.8, 132.6, 130 1, 156.0, 153.7, 134.0, 126.4, 125.8, 123.1, 118.0, 110.6 ppm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…2b Prepared according to the general procedure discussed above: eluent, EtOAc/n-hexane (20%); isolated yield = 0.042 g, 85%; white solid; 1 2-Phenyl-4H-chromen-4-one (2f). 2b Prepared according to the general procedure discussed above: eluent, EtOAc/n-hexane (20%); isolated yield = 0.047 g, 95%; white solid; 1 H NMR (600 MHz, CDCl 3 ) δ = 8.24 (d,J = 7.8 Hz,1 H),2 H),1 H),4 H),1 H), 6.83−6.84 ppm (m, 1 H); 13 C NMR (150 MHz, CDCl 3 ) δ = 179. 5, 164.4, 157.3, 134.8, 132.8, 132.6, 130 1, 156.0, 153.7, 134.0, 126.4, 125.8, 123.1, 118.0, 110.6 ppm.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…5c: EtOAc/n-hexane (3%); 0.008 g, 15%; yellow gum. 4c: 1 (d,J = 4.5 Hz,1 H),5.44 (d,J = 4.5 Hz,1 H), 2.10 ppm (s, 3 H); 13 C NMR (75 MHz, ) δ = 207.8, 140.0, 137.1, 134.4, 125.4, 124.5, 124.2, 123.0, 122.9, 75.3, 25.1 ppm; IR (KBr, cm −1 ) νÕ H = 3439, ν̃C O = 1717, ν̃m ax = 1428, 1356, 1102, 763, 735; HRMS (EI) m/z calcd for C 11 H 10 O 2 S [M] + : 206.0402; found: 206.0404. 5c: 1 H NMR (600 MHz, DMSO-d 6 ) δ = 9.01 (s, 1 H), 1 H),1 H),1 H),7.49 (td,J = 1.8,8.4 Hz,1 H), 2.49 ppm (s, 3 H); 13 C NMR (150 MHz,185.5,145.9,139.5,137.0,128.6,126.6,126.2,124.7,123.6,26.1 ppm;IR (KBr, ν̃C O = 1627, ν̃m ax = 1422, 1056, 750; HRMS (ESI) m/z calcd for C 11 H 8 O 2 SNa [M + Na] + 227.0143, found 227.0150.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have utilized H 2 O 2 as oxidant in the synthesis of p-benzoquinones. Minisci et al [10] have reported the oxidation of dihydroxybenzenes by H 2 O 2 in methanolic or aqueous solution of H 2 SO 4 , at room temperature in the presence of I 2 or HI as catalysts. A similar procedure has been utilized for the synthesis of p-quinones from 2,6-disubstituted phenols with high yields and selectivity, so this procedure is recommended as a valuable method also for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of hydroquinone does not contradict the usual order of formation of intermediates proposed by many authors (phenols, hydroquinones, benzoquinones, carboxylic acids then CO 2 and H 2 O respectively), because the formation of hydroquinone from benzoquinone is a reversible process. 30,31 Mineralisation is the main aim of the photodegradation of 1,4-BQ and this can be followed by measuring the total organic carbon.…”
Section: Effect Of Phmentioning
confidence: 99%